2020
DOI: 10.1007/s40122-020-00208-x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Its Association with Pain Severity and Multisite Pain: A Prospective 10.7-Year Study

Abstract: Introduction Sleep disturbance is often comorbid with chronic pain disorders, with emerging evidence suggesting a stronger effect of sleep disturbance on pain than vice versa; however, few studies have evaluated the long-term associations between sleep disturbance and pain. This study was to examine the associations of sleep disturbance with knee pain severity, number of painful sites (NPS) and persistent pain in a 10.7-year cohort study. Methods A total of 1099 communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Sleep disturbance has been linked to increased pain responses in animal and human studies ( 2 – 5 , 36 ). In this study, the group that was given Tualang honey showed a reduction of pain behaviour score in phase 2, but the reduction was only significant in late phase 2.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance has been linked to increased pain responses in animal and human studies ( 2 – 5 , 36 ). In this study, the group that was given Tualang honey showed a reduction of pain behaviour score in phase 2, but the reduction was only significant in late phase 2.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between sleep and pain appears to be dose dependent 25,28,29,35,38. An 11-year cohort study of older adults found a dose-dependent and reciprocal relationship between sleep disturbance and persistent pain severity and number of pain sites 29.…”
Section: Relationship Between Sleep and Painmentioning
confidence: 99%
“…A clinically relevant entity of multisite musculoskeletal pain (MSMP) has been defined, as musculoskeletal pain rarely occurs at single site [ 5 ]. More detrimental health outcomes associated with MSMP have been reported, such as health-related quality of life, fractures and sleep disturbance [ 6 , 7 , 8 , 9 , 10 ]. However, the initiation and persistence of MSMP is far from being fully understood.…”
Section: Introductionmentioning
confidence: 99%